2022
DOI: 10.1371/journal.pone.0273117
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescription acquisition of antibiotics: Prevalence, motives, pathways and explanatory factors in the Swedish population

Abstract: Prior studies indicate prevalence of unregulated non-prescription use of antibiotics also in the northern European countries. The aim of this study is to investigate the extent to which antibiotics are acquired without prescription in Sweden, and people’s attitudes and motives linked to this practice. We use data from an online survey of a representative sample of the Swedish general population which included questions about respondents’ antibiotic use, attitudes towards antibiotics, health care contacts, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A possible type of under-reporting that has been identified but is not considered as such in the reports originates in the legislation of some countries themselves. The acquisition of antibiotics without prescription, for instance, is a critical issue, even for countries that achieved their objective, have strong collecting systems, and have never officially underreported, like Sweden [10].…”
Section: Resultsmentioning
confidence: 99%
“…A possible type of under-reporting that has been identified but is not considered as such in the reports originates in the legislation of some countries themselves. The acquisition of antibiotics without prescription, for instance, is a critical issue, even for countries that achieved their objective, have strong collecting systems, and have never officially underreported, like Sweden [10].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a link between self-medication with antibiotics and distrust in healthcare was seen in a cohort of 4243 Swedish survey respondents. 8 Other studies have documented an association between trust in the healthcare provider and delay of antibiotics; however, there is limited data on the link between trust in the healthcare system and the use of antibiotics. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a link between selfmedication with antibiotics and distrust in healthcare was seen in a cohort of 4243 Swedish survey respondents. 8 Other studies have documented an association between trust in the healthcare provider and delay of antibiotics; however, there is limited data on the link between trust in the healthcare system and the use of antibiotics. 28,29 The overall distrust score among our survey respondents was a mean (SD) of 2.2 (0.6) or a composite score of 19.9 (15.9), which is moderate and falls between rates reported in studies in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in Sweden, a country with very strong legislation and regulation of antibiotics, a recent survey showed that 2.3% of the respondents had acquired antibiotics without prescription. 5 This will require careful attention to access to healthcare so children who require antibiotics can secure an appropriate drug at the correct dose for the ideal length of time after evaluation by a healthcare provider. An important point is to establish the early diagnosis of the infection, demanding the adequate taking of samples, the request for cultures and the use of molecular tools that identify the aetiology and avoid the inappropriate administration of antibiotics.…”
Section: The Need To Support Initiatives Related To Infection Control...mentioning
confidence: 99%